Bias Linguistik dan Kepercayaan Diri Berbahasa dalam Pembelajaran Bahasa Arab: Kajian Sosiolinguistik - Maulidya Harahap; Ade Nandang; Izzuddin Mustafa (INDO PUBLISHING, 2026)
This study examines the phenomenon of linguistic bias toward Arabic dialects and its impact on the linguistic confidence of Arabic language learners through a library research approach. Data were drawn from indexed journal articles, linguistics books, and relevant sociolinguistic studies, analyzed using content analysis with narrative synthesis. The findings indicate that linguistic bias against Arabic dialects constitutes a social construction shaped through mechanisms of overt and covert prestige, rather than intrinsic linguistic differences. This bias manifests in learning environments through four primary patterns: dialectal hierarchy, competence-dialect association, media representation dominance, and excessive correction. Psychologically, such bias diminishes linguistic confidence by heightening foreign language anxiety, fostering a negative linguistic self-concept, and reducing willingness to communicate. Conversely, learning environments that promote dialectal equality, reflective educator roles, and sociolinguistic literacy serve as protective factors for learners' linguistic confidence. This study contributes to the development of inclusive and linguistically just Arabic language pedagogy.